Multiple control of fever production in the central nervous system of rabbits. - Morimoto, A (1988)
1. The effects of microinjection of prostaglandin D2, E2 and F2 alpha and of endogenous pyrogen on the rectal temperature of rabbits were extensively examined in sixty-eight brain regions and in the third cerebral ventricle. 2. Intracerebroventricular injection of both prostaglandins E2 and F2 alpha produced dose-dependent fever over a range of 100-1000 ng. The selective brain regions, the nucleus broca ventralis, preoptic area, anterior hypothalamus and the ventromedial hypothalamus, responded to microinjections of a small dose (less than 200 ng) of prostaglandins E2 and F2 alpha by producing fever. Furthermore, the lateral hypothalamus, ventral thalamus, substantia nigra and the trigeminal nucleus were also sensitive to high concentrations of prostaglandins E2 and F2 alpha, fever being produced. It is likely that prostaglandin D2 is not involved in fever induction. 3. The ventricular injection of endogenous pyrogen also produced fever. However, brain regions sensitive to microinjection of endogenous pyrogen were exclusively localized to regions near the organum vasculosum laminae terminalis (OVLT), such as the nucleus broca ventralis and the preoptic area. In contrast to the monophasic fever induced by prostaglandins E2 and F2 alpha, about 30 min after ventricular or cerebral injection of endogenous pyrogen the rectal temperature gradually started to rise and the fever was prolonged over 4 h. 4. We investigated the effect of an inhibitor of prostaglandin synthesis, sodium salicylate, on biphasic fever induced by intravenous injection of bacterial endotoxin. The microinjections of sodium salicylate into the bilateral regions near the OVLT suppressed the second peak but had no effect on the first peak. 5. The present study clarifies that there exist two separate mechanisms of induction of biphasic fever. Correlating with the first peak of biphasic fever, prostaglandins synthesized outside the blood-brain barrier act on multiple sites in the central nervous system to induce fever. Correlating with the second peak, endogenous pyrogen acts on regions near the OVLT to synthesize and release pyrogenic prostaglandins.